GAMBARAN DUKUNGAN KELUARGA TERHADAP AKTIVITAS KEAGAMAAN PADA PASIEN SKIZOFRENIA DI KLINIK POLI RSJ GRHASIA YOGYAKARTA - Ari Budiati Sri Hidayati; Rinatalia; Laili Nur Hidayati (Jurnal Ilmiah Keperawatan, 2022)
Schizophrenia is a mental disorder that causes disturbances in thinking and behavior which results in decreased cognitive and social functions in a person. The support provided by the family to the patient is very important for the patient's recovery. This study aims to determine how the description of family support for religious activities in patients with schizophrenia at the Poli Clinic of RSJ Grhasia Yogyakarta. This study used a quantitative method with a cross sectional research design. The research sample consisted of 82 respondents who were taken using the Acidental Sampling technique. The results of this study indicate a description of family support for religious activities in schizophrenia patients in the good category, namely 77 respondents (93.9%) and sufficient, namely 5 respondents (6.1%). In conclusion, the description of family support for worship activities in schizophrenia patients is good.